2017
DOI: 10.1126/sciimmunol.aan8289
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the human antibody repertoire after B cell depletion in systemic sclerosis

Abstract: Systemic sclerosis with pulmonary arterial hypertension (SSc-PAH) is a debilitating and frequently lethal disease of unknown cause lacking effective treatment options. Lymphocyte anomalies and autoantibodies observed in systemic sclerosis have suggested an autoimmune character. We study the clonal structure of the B cell repertoire in SSc-PAH using immunoglobulin heavy chain (IGH) sequencing before and after B cell depletion. We found SSc-PAH to be associated with anomalies in B cell development, namely, alter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 43 publications
2
37
0
Order By: Relevance
“…The B‐cell depletion approach is an approved therapy for lymphoma patients and for some autoimmune diseases (Salles et al, ; Schioppo & Ingegnoli, ). A recent article has shown that B‐cell depletion in systemic sclerosis patients not only promotes remission but also temporarily reverses the disease‐restricted B‐cell repertoire due to new B‐cell generation (Bourcy, Dekker, Davis, & Nicolls, ). The present study proposes that this rejuvenation may be also induced in elderly population, where B lymphopoiesis is suppressed.…”
Section: Discussionmentioning
confidence: 99%
“…The B‐cell depletion approach is an approved therapy for lymphoma patients and for some autoimmune diseases (Salles et al, ; Schioppo & Ingegnoli, ). A recent article has shown that B‐cell depletion in systemic sclerosis patients not only promotes remission but also temporarily reverses the disease‐restricted B‐cell repertoire due to new B‐cell generation (Bourcy, Dekker, Davis, & Nicolls, ). The present study proposes that this rejuvenation may be also induced in elderly population, where B lymphopoiesis is suppressed.…”
Section: Discussionmentioning
confidence: 99%
“…An AIRR-seq investigation revealed that differential expression of IGHV genes in the repertoires from SSc cohorts relative to a healthy cohort are present in the IgD/IgM compartment. 84 These…”
Section: Toler An Ce Check P Oint Defec Ts Alter the Naive B-cell Rmentioning
confidence: 99%
“…81 ities. 84 These F I G U R E 4 Variable region family usage is skewed in the naive BCR repertoire of patients with myasthenia gravis who suffer from impaired early B-cell tolerance checkpoints. 84 These F I G U R E 4 Variable region family usage is skewed in the naive BCR repertoire of patients with myasthenia gravis who suffer from impaired early B-cell tolerance checkpoints.…”
Section: Toler An Ce Check P Oint Defec Ts Alter the Naive B-cell Rmentioning
confidence: 99%
“…Currently, targeted Adaptive Immune Receptor Repertoire sequencing assays (AIRR-seq) methods are routinely employed to sequence these transcripts and investigate the human immune system [20][21][22] . Specialized assays are required because the diversity and unique nature of these transcripts make them practically impossible to analyze at full length using standard RNA-seq protocols.…”
Section: Introductionmentioning
confidence: 99%